The Impact of Ngaha Aina Ngoho Local Wisdom on Preserving the Environment from an Ecoregion Perspective in Bima City - Taufiqurrahman, Taufiqurrahman; Kamlasi, Anjulin Yonathan; Ridwan, Ridwan (IJBLE Scientific Publications Community Inc., 2025)
The purpose of this study describes the impact of local wisdom Ngaha Aina Ngoho as the local cultural identity of the Bima community in preserving the environment from an ecoregion perspective. The research method used is the empirical legal method, which emphasizes the validity of the Bima Mayor's program with the Bima Bisa City Program (Clean, Beautiful, Healthy and Asri) and the Decree of the Mayor of Bima Number 33 of 2017 concerning Mutual Cooperation. The impact of local wisdom Ngaha Aina Ngoho as the local cultural identity of the Bima community provides positive results, including an increase in public awareness of preserving a clean environment. In addition, the Bima Bisa City program increases public awareness in disposing of garbage in its place and cleaning the environment. The Bima City program can provide community enthusiasm in carrying out mutual cooperation. In addition, collaboration between the government and indigenous communities and formal legal recognition of Ngaha Aina Ngoho are still minimal. Strategic efforts are needed to strengthen regulations, environmental education based on local culture, and the involvement of traditional leaders in policy formulation.